Streptococcus suis meningitis in adults in Vietnam. - Mai, N; Hoa, N; Nga, T; Linh, L; Chau, T; Sinh, D; Phu, N; Chuong, L; Diep, T; Campbell, J; Nghia, H; Minh, T; et al. (2008)
BACKGROUND: Streptococcus suis infection is an emerging zoonosis in Asia. We determined the detailed epidemiological, clinical, and microbiological characteristics of S. suis meningitis in adults. METHODS: We prospectively studied 450 patients with suspected bacterial meningitis. Four hundred thirty-five (96.7%) of the patients participated in a trial to determine the effect of adjunctive dexamethasone treatment. For patients with S. suis infection, bacterial DNA load at hospital admission and during treatment was analyzed in cerebrospinal fluid specimens using quantitative real-time polymerase chain reaction. S. suis strains were characterized using pulsed-field gel electrophoresis and multilocus sequence typing. Putative virulence factors, including extracellular protein factor, suilysin, and muramidase released protein, were detected using polymerase chain reaction and Western blot assay. Predictors of outcome were identified using logistic regression analysis. RESULTS: S. suis was the most common pathogen and was detected in 151 (33.6%) of the patients. Fifty (33.1%) of these 151 patients reported exposure to pigs or pork. Mortality was low (2.6%; 4 of 151 patients died), but mild to severe hearing loss occurred in 93 (66.4%) of 140 patients. Severe deafness at hospital discharge was associated with age >50 years (odds ratio, 3.65; 95% confidence interval, 1.15-11.6), a strain carrying the epf gene (odds ratio, 3.42; 95% confidence interval, 1.02-11.4), and dexamethasone therapy (odds ratio, 0.23; 95% confidence interval, 0.06-0.78) but was not associated with cerebrospinal fluid bacterial DNA load. Bacterial DNA was still detectable in 58 (63%) of 92 cerebrospinal fluid samples after 6-10 days of antimicrobial treatment. Ninety-one of 92 S. suis strains had serotype 2. Thirty-three (36%) of these epidemiologically unrelated strains belonged to 1 pulsed-field gel electrophoresis cluster of multilocus sequence type 1, indicating clonal spread. CONCLUSION: S. suis serotype 2 is the most frequent cause of bacterial meningitis in adults in southern Vietnam and is associated with substantial morbidity attributable to hearing loss.